TRANSPOSITION AND MODULATION OCCURRED IN THE TRANSLATION OF MEITANTEI CONAN MANGA VOLUME 61: ANALISIS PERGESERAN BENTUK DAN PERGESERAN MAKNA DALAM TERJEMAHAN MANGA MEITANTEI CONAN VOLUME 61 - Yuniarsih Yuniarsih; Eky Kusuma Hapsari; Andra Roni Kusuma (Jurnal Kata, 2022)
The aim of this study is to determine the type of transposition and modulation that occurred in the manga: Meitantei Conan, and translation process of the occurred transposition and modulation. This study uses a transposition classification based on the theory of Catford, modulation based on the theory of Vinay and Dabelnet, and translation process based on the theory Nida and Taber. This study uses “Simak” method for collecting the data and Padan Translational method for analysis the data. Based on the analysis result, there are 44 data of sentences which transposition and modulation occurred. There are 32 data of transpositions and 13 data of modulations. Also, there are 5 data which transposition and modulation occurred on the same sentences. The most of transpositions data goes to unit shift category, and the most of modulations data goes to reversal of terms category. These happened because there are many words and terms that can not be directly translated to “Bahasa” because of cultural differences.